THE ROLE OF SOCIAL NETWORKS IN ACCESS TO JUSTICE: BRIDGING LAW AND SOCIETY - Mongdong, Novita; Wereh, Agustien Cherly; Palempung, Leidy; Mesra, Romi (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
This study aims to explore the role of social networks in facilitating access to justice in Indonesia, focusing on how individuals and communities use their social connections to understand, access, and navigate the legal system. Using a qualitative approach, this study combines fieldwork in three different locations in Indonesia (urban, rural, and remote areas) with a comprehensive literature review. Data collection methods include in-depth interviews, participant observation, and document analysis. The results show that social networks play a crucial role in three main aspects: dissemination of legal information, mobilization of resources, and formation of legal problem-solving strategies. However, the effectiveness of social networks in facilitating access to justice varies depending on geographic and socio-cultural contexts. The study also reveals tensions between community-based conflict resolution mechanisms and the formal justice system, as well as the transformation of the role of social networks due to digitalization. These findings emphasize the need for a more holistic and contextual approach to improving access to justice in Indonesia, taking into account the complex dynamics of social networks.